2010
DOI: 10.1186/1756-0500-3-174
|View full text |Cite
|
Sign up to set email alerts
|

Relatively higher norms of blood flow velocity of major intracranial arteries in North-West Iran

Abstract: BackgroundTranscranial Doppler (TCD) is a noninvasive, less expensive and harmless hemodynamic study of main intracranial arteries. The aim of this study was to assess normal population values of cerebral blood flow velocity and its variation over age and gender in a given population.FindingsEighty healthy volunteers including 40 people with an age range of 25-40 years (group1) and 40 persons with an age range of 41-55 years (group2) were studied. In each group 20 males and 20 females were enrolled. Peak systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Our findings were similar to the general trends found in most other studies, 18‐28 although some authors found no association between age and cerebral blood flow velocities 29‐31 . The variations in MBFV by age may be because of decreased metabolic demands, higher hematocrit, or changes in the cerebrovascular hemodynamics during the aging process, and changes of cerebral autoregulation with age as a result of the accumulation of vascular risk factor burden and autonomic abnormalities 32 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings were similar to the general trends found in most other studies, 18‐28 although some authors found no association between age and cerebral blood flow velocities 29‐31 . The variations in MBFV by age may be because of decreased metabolic demands, higher hematocrit, or changes in the cerebrovascular hemodynamics during the aging process, and changes of cerebral autoregulation with age as a result of the accumulation of vascular risk factor burden and autonomic abnormalities 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Our study did not show any significant differences in MFBV from dominant to nondominant side based on handedness. Higher velocities on the left have been reported by others, 22,30,31 because of the dominance of the left hemisphere or lack of adequate rest between stimulation of the patient and initiation of the exam. The greater variability in cerebral blood flow velocities on the left side of the Circle of Willis may explain the lack of hemispheric differences of velocities in our study.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The standard method of using a 2 mHz probe for the intracranial arteries and a 4 mHz probe for the cervical carotids was applied in the present study. The Doppler signals were detected through the temporal window for the middle cerebral artery, anterior cerebral artery and two segments of the posterior cranial artery (PCA 1 , PCA 2 ), through the suboccipital window for the vertebral arteries and basilar artery, and through the cervical window for the internal carotid arteries 14. Mean blood flow velocity, pulsatility index, and resistance index were recorded in all the arteries 1517…”
Section: Methodsmentioning
confidence: 99%